Confessional Conflicts as A Form Of Social Disputes - Latifovich, Sattiyev Muzaffar (Pubmedia Social Sciences and Humanities, 2024)
The article examines confessional conflicts as a form of social conflict in multi-ethnic and multi-religious societies. The reasons for the origin of confessional conflicts, stages of development and methods of their resolution are analyzed. The author details cultural pluralism and the struggle for economic and political supremacy between denominations, as well as the impact of these conflicts on societal stability. Different models of conflict resolution are considered and their positive and negative aspects are analyzed. The main idea of the article is that the resolution of confessional disputes is important in maintaining and developing social and political stability of society.